Structural analysis of technical-tactical elements in table tennis and their role in different playing zones - Munivrana, G.; Zekan Petrinovic, L.; Kondric, M. (Journal of Human Kinetics, 2015)
For the purpose of determining the overall structure of technical-tactical elements in table tennis and evaluating their role in different playing zones around the table, a new measuring instrument (a questionnaire) was formulated that took advantage of the expert knowledge of top, world class table tennis coaches. The results of the hierarchical taxonomic (cluster) analysis showed that the overall structure of the technical-tactical elements forming the table tennis technique could be divided into three basic groups; a group of technical-tactical elements (A) used in the phase of preparing one`s own and disabling the opponent`s attack; a group of technical-tactical elements (B) used in the phase of attack and counterattack; and a group of technical-tactical elements (C) used in the phase of defense. The differences among the obtained groups of table tennis elements were determined by applying the Kruskal-Wallis test, while relations between the groups and their role in different playing zones around the table were analyzed by comparing the average values of the experts` scores.